Negative electrode sheet, method for manufacturing the same, electrochemical device, and electronic device

CN117157776BActive Publication Date: 2026-10-09NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280027250.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-01
Publication Date
2026-10-09
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

[0003]但是,由于受到负极活性材料的限制,电化学装置的能量密度普遍较低

Benefits of technology

[0029]The negative electrode of this application includes a negative current collector and a negative active material layer. The negative active material layer includes a first active material layer and a second active material layer. The first active material layer includes silicon-based particles. Due to the high theoretical specific capacity of silicon-based particles, the reversible specific capacity of the negative electrode is high. Furthermore, when the negative electrode of this application is used as an electrochemical device, the electrochemical device has a high energy density. Moreover, the first active material layer is disposed between the second active material layer and the negative current collector. The first active material layer has a first through-hole, and a portion of the second active material layer passes through the first through-hole and contacts the negative current collector. The negative active material layer of this application is a novel double-layer structure formed by the second active material layer located on the outer side and the first active material layer located on the inner side that does not completely cover the negative current collector. The second active material layer contacts the surface of the negative current collector through the first through-hole, providing an additional current channel for the second active material layer and reducing the impedance of the electrochemical device. Furthermore, the rate capability and cycle performance of the second active material layer containing carbon-based particles are superior to those of the first active material layer containing silicon-based particles. The second active material layer directly contacts the negative electrode current collector through the first through-hole, effectively leveraging its advantages in rate capability and cycle performance. This mitigates the drawback of the first active material layer, which contains a high amount of highly adhesive first binder, leading to reduced electrical performance. In addition, the novel double-layer structure eliminates the poor electrical performance of the first active material layer to some extent, reducing its impact on the charge/discharge and cycle performance of the second active material layer and the electrochemical device. The above description is merely an overview of the technical solution of this application. To better understand the technical means of this application and to implement it according to the description, and to make the above and other objects, features, and advantages of this application more apparent, specific embodiments of this application are described below.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117157776B_ABST
    Figure CN117157776B_ABST
Patent Text Reader

Abstract

The application relates to a negative electrode sheet, a preparation method thereof, an electrochemical device and a power utilization device. The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer comprises a first active material layer and a second active material layer. The first active material layer is arranged on the surface of the negative electrode current collector, and the first active material layer comprises a plurality of first through holes arranged at intervals and penetrating through the first active material layer in the thickness direction of the negative electrode current collector. The second active material layer is arranged on at least the surface of the negative electrode current collector. The first active material layer is arranged between the second active material layer and the negative electrode current collector. The first active material layer comprises silicon-based particles, and the second active material layer comprises carbon-based particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage technology, and more specifically, to negative electrode sheets and their preparation methods, electrochemical devices, and electronic devices. Background Technology

[0002] Electrochemical devices, characterized by high energy density, high operating voltage, and light weight, are widely used in electronic products such as mobile phones, laptops, and cameras. While improving the electrochemical performance of these devices is crucial, other performance aspects are equally important. As the performance requirements for electronic products increase, the performance requirements for electrochemical devices also gradually rise.

[0003] However, due to limitations in the negative electrode active materials, the energy density of electrochemical devices is generally low. Therefore, the energy density of existing electrochemical devices still needs to be improved. Summary of the Invention

[0004] This application provides a negative electrode sheet and its preparation method, an electrochemical device, and an electronic device, which can improve the energy density of the electrochemical device.

[0005] In a first aspect, this application proposes a negative electrode sheet, comprising a negative current collector and a negative active material layer. The negative active material layer includes a first active material layer and a second active material layer. The first active material layer is disposed on the surface of the negative current collector and includes a plurality of spaced first through-holes extending through the first active material layer along the thickness direction of the negative current collector. The second active material layer is disposed on the surface of the first active material layer and at least partially extends through the first through-holes to contact the surface of the negative current collector. The first active material layer comprises silicon-based particles; the second active material layer comprises carbon-based particles.

[0006] In some embodiments of this application, the negative electrode current collector includes two surfaces opposite each other along its own thickness direction; a negative electrode active material layer is disposed on the two surfaces of the negative electrode current collector.

[0007] In some embodiments of this application, the second active material layer includes a base layer and an extension connected to the base layer and protruding relative to the base layer. The base layer is disposed on the surface of the first active material layer opposite to the negative electrode current collector, and the extension is disposed in the first through hole and extends to the surface of the negative electrode current collector.

[0008] In some embodiments of this application, the negative electrode current collector includes a plurality of second through holes disposed at intervals through the negative electrode current collector along the thickness direction of the negative electrode current collector. The second through holes communicate with the first through holes, and the extension extends into the second through holes.

[0009] In some embodiments of this application, the opening shapes of each first through hole and second through hole are independently selected from rectangles, squares, circles, ellipses, rhombuses, cones, strips, or triangles.

[0010] In some embodiments of this application, the area S1 of the first active material layer covering the negative electrode current collector and the area S0 of the negative electrode current collector satisfy 60% ≤ S1 / S0 ≤ 90%.

[0011] In some embodiments of this application, the area S1 of the first active material layer covering the negative electrode current collector and the area S0 of the negative electrode current collector satisfy 70% ≤ S1 / S0 ≤ 80%.

[0012] In some embodiments of this application, the silicon-containing particles in the first active material layer account for 50% to 98% of the total mass of the first active material layer, and optionally 60% to 95%.

[0013] In some embodiments of this application, the silicon-based particles are selected from one or more of elemental silicon, silicon alloys, silicon-carbon composites, and silicon oxide materials.

[0014] In some embodiments of this application, the carbon-based particles are selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, and mesophase carbon microspheres.

[0015] In some embodiments of this application, the negative electrode sheet satisfies one or more of the following (1) to (4):

[0016] (1) The first active material layer further includes a first adhesive, which is selected from one or more of polypropylene, polyacrylate, acrylonitrile copolymer and carboxymethyl cellulose salt, and optionally the first adhesive is selected from a polymer of one or more monomers of acrylonitrile, acrylate, acrylamide and acrylate.

[0017] (2) The thickness of the first active material layer is 3 μm to 12 μm, preferably 3 μm to 6 μm;

[0018] (3) The adhesion force between the first active material layer and the negative electrode current collector is greater than or equal to 150 N / m;

[0019] (4) The ratio of the single-sided unit area capacity of the first active material layer to that of the second active material layer is 1:(1-4).

[0020] Secondly, embodiments of this application provide a method for preparing a negative electrode sheet, comprising:

[0021] A first active slurry containing at least silicon-based particles is provided, and a first active material layer is formed on a negative electrode current collector by the first active slurry to obtain a composite, wherein the first active material layer includes a plurality of first through holes disposed at intervals through the first active material layer along the thickness direction of the negative electrode current collector.

[0022] A second active slurry containing at least carbon-based particles is provided, and a second active material layer is formed on a composite by the second active slurry to obtain a negative electrode sheet, wherein the second active material layer is at least disposed on the surface of the negative electrode current collector.

[0023] In some embodiments of this application, the negative electrode current collector is provided with a plurality of spaced-apart second through holes, and the method for preparing the second through holes includes:

[0024] A hole is created in the negative electrode current collector to obtain a negative electrode current collector with a second through hole.

[0025] In some embodiments of this application, the negative electrode current collector is provided with a plurality of spaced-apart second through holes, and the method for preparing the second through holes includes:

[0026] The composite is pore-formed to obtain a negative electrode current collector with a second through hole, and a first through hole is formed on the first active material layer.

[0027] Thirdly, embodiments of this application provide an electrochemical device, including a negative electrode sheet as described in any of the embodiments of the first aspect above, or a negative electrode sheet prepared by any of the preparation methods described in any of the embodiments of the second aspect above.

[0028] Fourthly, embodiments of this application provide an electrical device, including the electrochemical device in any of the embodiments of the third aspect described above.

[0029] The negative electrode of this application includes a negative current collector and a negative active material layer. The negative active material layer includes a first active material layer and a second active material layer. The first active material layer includes silicon-based particles. Due to the high theoretical specific capacity of silicon-based particles, the reversible specific capacity of the negative electrode is high. Furthermore, when the negative electrode of this application is used as an electrochemical device, the electrochemical device has a high energy density. Moreover, the first active material layer is disposed between the second active material layer and the negative current collector. The first active material layer has a first through-hole, and a portion of the second active material layer passes through the first through-hole and contacts the negative current collector. The negative active material layer of this application is a novel double-layer structure formed by the second active material layer located on the outer side and the first active material layer located on the inner side that does not completely cover the negative current collector. The second active material layer contacts the surface of the negative current collector through the first through-hole, providing an additional current channel for the second active material layer and reducing the impedance of the electrochemical device. Furthermore, the rate capability and cycle performance of the second active material layer containing carbon-based particles are superior to those of the first active material layer containing silicon-based particles. The second active material layer directly contacts the negative electrode current collector through the first through-hole, effectively leveraging its advantages in rate capability and cycle performance. This mitigates the drawback of the first active material layer, which contains a high amount of highly adhesive first binder, leading to reduced electrical performance. In addition, the novel double-layer structure eliminates the poor electrical performance of the first active material layer to some extent, reducing its impact on the charge / discharge and cycle performance of the second active material layer and the electrochemical device. The above description is merely an overview of the technical solution of this application. To better understand the technical means of this application and to implement it according to the description, and to make the above and other objects, features, and advantages of this application more apparent, specific embodiments of this application are described below. Attached Figure Description

[0030] The accompanying drawings, necessary for describing embodiments of this application or the prior art, will be briefly described below to facilitate the depiction of embodiments of this application. It is obvious that the drawings described below represent only a portion of the embodiments in this application. Those skilled in the art will be able to derive other embodiments from the structures illustrated in these drawings without requiring inventive effort.

[0031] Figure 1 This is a partial structural schematic diagram of the negative electrode sheet provided in some embodiments of this application;

[0032] Figure 2 This is a front view of the first active material layer of the negative electrode sheet provided in some embodiments of this application;

[0033] Figure 3 This is a partial front view of the negative electrode sheet provided in some embodiments of this application;

[0034] Figure 4 This is a partial cross-sectional structural diagram of the negative electrode sheet provided in some embodiments of this application;

[0035] Figure 5 yes Figure 4 A schematic diagram of the structure of the negative electrode aa;

[0036] Figure 6 yes Figure 4 A schematic diagram of the negative electrode plate bb;

[0037] Figure 7 This is a schematic diagram of the negative current collector and the first active material layer of the negative electrode sheet provided in some embodiments of this application;

[0038] Figure 8 This is a schematic diagram of the negative current collector and the first active material layer of the negative electrode sheet provided in other embodiments of this application;

[0039] Figure 9 This is a schematic diagram of the negative current collector and the first active material layer of the negative electrode sheet provided in some embodiments of this application;

[0040] Figure 10 This is a schematic diagram of the negative current collector and the first active material layer of the negative electrode sheet provided in some other embodiments of this application;

[0041] Figure 11 This is a schematic diagram of the negative current collector and the first active material layer of the negative electrode sheet provided in some embodiments of this application;

[0042] Figure 12 This is a partial structural diagram of the negative electrode sheet including the second through hole provided in some embodiments of this application.

[0043] The accompanying drawings are not drawn to scale.

[0044] The following are the labeling elements in the figure:

[0045] 100. Negative electrode plate;

[0046] 10. Negative electrode current collector; 11. Second through hole;

[0047] 20. Negative electrode active material layer; 21. First active material layer; 211. First through hole; 22. Second active material layer; 221. Base layer; 222. Extension. Detailed Implementation

[0048] Embodiments of this application will be described in detail below. Throughout this specification, identical or similar components and components having identical or similar functions are indicated by similar reference numerals. The embodiments described herein with reference to the accompanying drawings are illustrative and diagrammatic in nature and are intended to provide a basic understanding of this application. The embodiments of this application should not be construed as limiting this application.

[0049] Additionally, quantities, ratios, and other numerical values ​​are sometimes presented in range format in this document. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or subranges covered within the range, as if each numerical value and subrange were explicitly specified.

[0050] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "one or more of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0051] The grouping of alternative elements or embodiments disclosed herein should not be construed as limiting. Each member of a group may be adopted and claimed individually, or in any combination with other members of that group or other elements found herein. It is foreseeable that one or more members of a group may be included in or removed from the group for convenience and / or patentability reasons.

[0052] Various modifications and variations can be made to this application without departing from its scope of protection, which will be obvious to those skilled in the art. Therefore, this application is intended to cover modifications and variations falling within the scope of the corresponding claims (the claimed scope) and their equivalents. It should be noted that the implementation methods provided in the embodiments of this application can be combined with each other without contradiction.

[0053] Before explaining the scope of protection provided by the embodiments of this application, in order to facilitate the understanding of the embodiments of this application, this application first specifically describes the problems existing in the related technology.

[0054] Batteries are widely used in electronic products such as mobile phones, tablets, and drones. People are placing increasingly higher demands on the battery capacity of these products, and increasing battery capacity within limited space requires higher energy density. Currently used graphite has a theoretical specific capacity of only 372 mAh / g, which cannot meet the demand for higher energy density; while silicon material has a maximum theoretical specific capacity of 4200 mAh / g, 10 times higher than graphite. Using silicon material can significantly improve battery energy density and is hailed as the next-generation battery anode material. However, in lithium-ion batteries, silicon material experiences significant volume expansion (>300%) during high-level lithium intercalation. This expansion of the anode sheet leads to pulverization and material loss, poor adhesion between anode materials, repeated destruction and growth of the SEI on the anode surface, consumption of large amounts of electrolyte, and the generation of increasing side reactions, ultimately resulting in decreased cycle performance. The large volume expansion of silicon material during battery cycling limits its development; therefore, it is necessary to improve the expansion problem of silicon material during cycling.

[0055] Therefore, the inventors attempted to use nanoscale silicon materials, such as SiO and SiC. Nanoscale silicon materials have advantages such as large specific surface area, short ion diffusion paths, strong creep, and high plasticity, resulting in small volume changes during charge and discharge, which can alleviate the volume effect to some extent. However, the inventors further discovered that the theoretical specific capacity of silicon composite materials such as SiO and SiC is lower than that of elemental Si, and the actual reversible specific capacity is even lower. For example, the specific capacity of SiO is about 2400 mAh / g, and the actual reversible specific capacity is about 1500 mAh / g. Moreover, the initial charging efficiency of silicon composite materials is low, generally less than 80%. The inventors also tried to use Sn-based composite materials. Sn is similar to Si in that it has a high lithium storage capacity. However, due to its high cost and the difficulty in achieving uniformity in its coating process, it does not have an advantage over silicon materials.

[0056] In view of this, the inventors used a strong adhesive to restrain the expansion of silicon. However, the addition of a strong adhesive increases the internal resistance of the battery, thereby weakening its electrical performance. Therefore, this application addresses this issue by improving the negative electrode structure. A first active material layer is disposed between the second active material layer and the negative current collector. The first active material layer has a first through-hole, and a portion of the second active material layer passes through the first through-hole and contacts the negative current collector, providing an additional current channel for the second active material layer, reducing the impedance of the electrochemical device, and thus reducing the internal resistance of the electrochemical device. Simultaneously, the second active material layer directly contacts the negative current collector through the first through-hole, effectively leveraging the rate capability and cycle performance advantages of the second active material layer, thereby mitigating the low electrical performance of the first active material layer. The technical solution of this application will now be described in detail.

[0057] In this application, the electrochemical device includes any device in which an electrochemical reaction occurs, and specific examples include all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. For example, the electrochemical device is a lithium secondary battery, which may include lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.

[0058] Negative electrode sheet

[0059] This application proposes a negative electrode plate, such as Figures 1 to 3 As shown, the negative electrode 100 includes a negative current collector 10 and a negative active material layer 20. The negative active material layer 20 includes a first active material layer 21 and a second active material layer 22. The first active material layer 21 is disposed on the surface of the negative current collector 10 and includes a plurality of spaced first through-holes 211 extending through the first active material layer 21 along the thickness direction of the negative current collector 10. The second active material layer 22 is disposed at least on the surface of the negative current collector 10, and the first active material layer 21 is disposed between the second active material layer 22 and the negative current collector 10. The first active material layer 21 includes silicon-based particles; the second active material layer 22 includes carbon-based particles.

[0060] The negative electrode current collector 10 has a negative electrode active material layer disposed thereon. The negative electrode current collector 10 can collect and output the current generated by the negative electrode active material layer 20, and can also input current to the negative electrode active material layer. The negative electrode current collector 10 can be a metal foil or a porous metal plate, such as a foil or porous plate of metals or alloys thereof, such as copper, nickel, titanium, iron, etc. The negative electrode current collector 10 includes two surfaces that are opposite to each other along its own thickness direction. The negative electrode active material layer can be disposed on both surfaces, or it can be disposed on only one of the two surfaces.

[0061] In some embodiments of this application, the negative current collector 10 is a copper foil with a thickness of 4 μm to 15 μm.

[0062] The negative electrode active material layer 20 includes a first active material layer 21 and a second active material layer 22. The first active material layer 21 includes a first through-hole 211 penetrating the negative electrode current collector 10 along its thickness direction, and includes silicon-based particles. These silicon-based particles contain silicon and may also contain carbon, oxygen, nitrogen, phosphorus, sulfur, etc. The second active material layer 22 is at least disposed on the surface of the negative electrode current collector 10, and the first active material layer 21 is disposed between the second active material layer 22 and the negative electrode current collector 10. This can be understood as follows: a portion of the second active material layer 22 is disposed on the side of the first active material layer 21 facing away from the negative electrode current collector 10, and another portion is disposed within the first through-hole 211 and in contact with the negative electrode current collector 10. The carbon-based material contains carbon, and the silicon-based particles may also contain nitrogen, oxygen, etc.

[0063] In the embodiments of this application, there are multiple first through holes 211 in the first active material layer 21, and the multiple first through holes 211 are spaced apart on the first active material layer 21.

[0064] The negative electrode active material layer 20 of this application includes a first active material layer 21 and a second active material layer 22. The first active material layer 21 comprises silicon-based particles. Due to the high theoretical specific capacity of silicon-based particles, the reversible specific capacity of the negative electrode is high. Furthermore, when the negative electrode of this application is used as an electrochemical device, the electrochemical device exhibits a high energy density. Moreover, the first active material layer 21 is disposed between the second active material layer 22 and the negative electrode current collector 10. The first active material layer 21 has a first through-hole 211, and a portion of the second active material layer 22 is disposed in the first through-hole 211 and contacts the negative electrode current collector 10. The negative electrode active material layer 20 of this application is a novel double-layer structure formed by the second active material layer 22 located on the outer side and the first active material layer 21 located on the inner side, which does not completely cover the negative electrode current collector 10. The second active material layer 22 contacts the surface of the negative electrode current collector 10 through the first through-hole 211, providing an additional current channel for the second active material layer 22 and reducing the impedance of the electrochemical device. Furthermore, the rate capability and cycle performance of the second active material layer 22 containing carbon-based particles are superior to those of the first active material layer 21 containing silicon-based particles. The second active material layer 22 is in direct contact with the negative electrode current collector 10 through the first through-hole 211, effectively leveraging its advantages in rate capability and cycle performance. This mitigates the drawback of the first active material layer 21, which contains a high amount of highly adhesive first binder and suffers from low electrical performance. In addition, the novel double-layer structure can, to some extent, eliminate the poor electrical performance of the first active material layer 21, reducing the impact of the second active material layer 22 and the charge / discharge and cycle performance of the electrochemical device.

[0065] In some embodiments of this application, the negative electrode current collector 10 includes two surfaces facing each other along its own thickness direction. A negative electrode active material layer 20 is disposed on both surfaces of the negative electrode current collector 10. The negative electrode active material layer 20 includes a first active material layer 21 and a second active material layer 22. The negative electrode active material layer 20 is disposed on both surfaces of the negative electrode current collector 10, which can be understood as including, along the thickness direction of the negative electrode current collector 10, the second active material layer 22, the first active material layer 21, the negative electrode current collector 10, the first active material layer 21, and the second active material layer 22 in sequence. A portion of the second active material layer 22 located on both sides of the negative electrode current collector 10 is in contact with the negative electrode current collector 10 through the first active material layer 21. This arrangement results in a more significant increase in energy density.

[0066] See also Figures 4 to 6 , Figure 4 This is a partial cross-sectional structural diagram of the negative electrode sheet provided in some embodiments of this application; Figure 5 yes Figure 4 A cross-sectional schematic diagram of the negative electrode aa; Figure 6 yes Figure 4 A schematic cross-sectional view of the negative electrode plate (bb).

[0067] In some embodiments of this application, such as Figures 4 to 6 As shown, the second active material layer 22 includes a base layer 221 and an extension 222 connected to the base layer 221 and protruding relative to the base layer 221. The base layer 221 is disposed on the surface of the first active material layer 21 facing away from the negative electrode current collector 10. The extension 222 is disposed within the first through hole 211 and extends to the surface of the negative electrode current collector 10. The second active material layer 22 includes a base layer 221 and an extension 222. The first active material layer 21 has a first through hole 211 for accommodating the extension 222. The base layer 221 is stacked on the first active material layer 21. The extension 222 is connected to the hole wall of the first through hole 211 and contacts the negative electrode current collector 10. The extension 222 in the second active material layer 22 directly contacts the negative electrode current collector 10 through the first through hole 211, which can effectively utilize the rate capability and cycle performance advantages of the second active material layer 22.

[0068] In some embodiments, the extension 222 fills the gap in the first through-hole 211 and contacts the negative electrode current collector 10. With this configuration, the second active material layer 2 directly contacts the negative electrode current collector 10 through the first through-hole 211, effectively leveraging the rate capability and cycle performance advantages of the second active material layer 22.

[0069] In some embodiments, the first through hole 211 located on one side of the negative electrode current collector 10 is disposed opposite to the first through hole 211 located on the other side of the negative electrode current collector 10.

[0070] In some other embodiments, the first through hole 211 located on one side of the negative electrode current collector 10 is misaligned with the first through hole 211 located on the other side of the negative electrode current collector 10.

[0071] In some embodiments of this application, the first active material layer 21 includes a plurality of first through holes 211, which are spaced apart. The presence of multiple first through holes 211 on the first active material layer 21 increases the contact area between the first active material layer 21 and the second active material layer 22, further enhancing the connection stability between them. Moreover, the spaced-apart first through holes 211 allow the extension portion 222 to cover a wider area, resulting in better rate and cycle performance of the second active material layer 22 compared to the first active material layer 21. The second active material layer 22 directly contacts the negative electrode current collector 10 through the uncoated first through holes 211, more effectively leveraging its advantages in rate and cycle performance without significantly reducing the degradation of the electrical performance of the first active material layer 21. Furthermore, the insertion of the extension portion 222 into the first through holes 211 can absorb and buffer the stress generated by the volume expansion of the first active material layer 21 to a certain extent, improving the connection stability of the first active material layer 21.

[0072] For example, multiple first through holes 211 are arranged at equal intervals. This arrangement makes the first through holes 211 more evenly distributed, improves the connection stability between the first active material layer 21 and the second active material layer 22, and is more conducive to giving full play to the advantages of the second active material layer 22 in terms of rate capability and cycle performance.

[0073] For example, the opening areas of the multiple first through holes 211 are equal. This arrangement allows the excellent activity of the first active material layer 21 to maintain the overall activity of the battery cell, while also utilizing the high energy density of the second active material layer 22 to achieve uniform overall energy density. Furthermore, the binding forces of each extension 222 on the first active material layer 21 are similar, ensuring that the first active material layer 21 has a uniform volume expansion rate, thus reducing local volume expansion differences and preventing powder shedding.

[0074] In some embodiments of this application, the opening shape of each first through hole 211 is selected from rectangles, squares, circles, ellipses, rhombuses, cones, strips, or triangles. The above opening shapes are conventional structures, which are convenient for production and processing.

[0075] For example, the openings of the multiple first through holes 211 are identical, such as circular, which can improve production efficiency and processing performance.

[0076] In this application, in order to observe the morphological features of the first active material layer 21, the second active material layer 22 can be peeled off from the first active material layer 21 by means of peeling, such as by adhesive tape, so as to peel the second active material layer 22 off from the first active material layer 21 and expose the first active material layer 21.

[0077] In this application, the tape peeling method specifically includes: (1) cutting the negative electrode sheet coated with the first active material layer 21 and the second active material layer 22 into strips with a length of 120 mm and a width of 20 mm; (2) attaching a double-sided tape with a length of about 100 mm and a width of 25 mm onto the plate; (3) attaching the cut negative electrode sheet coated with the first active material layer 21 and the second active material layer 22 onto the double-sided tape, leaving a suitable length at one end of the negative electrode sheet that is not attached to the double-sided tape to facilitate the peeling of the membrane, and pressing the negative electrode sheet appropriately so that the negative electrode sheet is attached to the double-sided tape and the double-sided tape is attached to the plate; (4) pulling up the negative electrode sheet from the end of the negative electrode sheet that is not attached to the double-sided tape and peeling it off. For the negative electrode sheet, since the adhesion between the second active material layer 22 and the first active material layer 21, and between the second active material layer 22 and the negative current collector 10 is much weaker than the adhesion between the first active material layer 21 and the negative current collector 10, the second active material layer 22 will be peeled off and left on the tape, while the first active material layer 21 will remain on the negative current collector 10, exposing the morphology of the first active material layer 21; in particular, if the adhesion of the second active material layer 22 itself is too weak, causing the tape to peel off from between the second active material layers 22, steps (3) and (4) can be repeated on the peeled negative electrode sheet until the first active material layer 21 and the current collector not coated with the first active material layer 21 are exposed.

[0078] In this application, the cross-section of the negative electrode sheet is obtained by methods such as electron beam cutting or circular knife slicing. Observation under a scanning electron microscope shows... Figure 5 and Figure 6 As shown, the layer with relatively smaller particles is the first active material layer 21 containing silicon-based particles, and the layer with relatively larger particles is the second active material layer 22 containing carbon-based particles. Further details can be found in the attached diagram. Figure 5 First through-holes 211 are spaced apart on the first active material layer 21. An extension 222 of the second active material layer 22 contacts the negative electrode current collector 10 through the first through-holes 211, and the second active material layer 22 completely covers the first active material layer 21. See further details. Figure 6 The first active material layer 21 is continuously disposed on the negative electrode current collector 10, and the second active material layer 22 completely covers the first active material layer 21.

[0079] In this application, as Figures 7 to 11 As shown, multiple first through holes 211 form island-shaped patterns, mesh patterns, sheet-like patterns, and other pattern effects.

[0080] See also Figure 12 , Figure 12 This is a partial structural diagram of the negative electrode sheet including the second through hole provided in some embodiments of this application.

[0081] In some embodiments of this application, such as Figure 12 As shown, the negative electrode current collector 10 includes a plurality of second through holes 11 disposed at intervals along the thickness direction of the negative electrode current collector 10. The second through holes 11 communicate with the first through hole 211, and the extension portion 222 extends into the second through hole 11.

[0082] The negative electrode current collector 10 has a second through hole 11 that communicates with the first through hole 211. An extension 222 extends into the second through hole 11. The second active material layers 22 located on both sides of the negative electrode current collector 10 are connected through the second through hole 11 and the first through hole 211, providing an additional current path for the outer second active material layers 22. Compared to a negative electrode sheet without through holes that includes the first active material layer 21 and the second active material layer 22, this reduces the impedance of the electrochemical device and eliminates the impact of the poor electrical performance of the first active material layer 21 on the charge / discharge and cycle performance of the second active material layer 22 and the overall electrochemical device. Furthermore, compared to a negative electrode sheet without through holes that includes the first active material layer 21 and the second active material layer 22, the current collector layer with the second through hole 11 not only reduces the weight of the current collector but also provides additional space for the negative electrode active material layer 20 to attach, further improving the energy density of the electrochemical device. Multiple second through holes 11 are spaced apart, and the second active material layers 22 on both sides are connected through the second through holes 11 of the negative electrode current collector 10 to form an integral structure, thereby further enhancing the overall structural stability of the second active material layers 22.

[0083] In some embodiments, the second through hole 11 is connected to the first through hole 211, and the opening area of ​​the first through hole 211 and the opening area of ​​the second through hole 11 may be equal or unequal in the thickness direction.

[0084] Optionally, the opening area of ​​the first through hole 211 is equal to the opening area of ​​the second through hole 11. This facilitates the integrated processing of the two, improving processing efficiency.

[0085] In some embodiments of this application, the opening shape of each second through hole 11 is selected from rectangle, square, circle, ellipse, rhombus, cone, strip, or triangle. The opening shape of the second through hole 11 may be the same as the opening shape of the first through hole 211.

[0086] Optionally, the opening shape of each second through hole 11 is circular. With this configuration, compared to other shapes, the circular shape of the second through hole 11 is easier to process and manufacture because other shapes may have sharp corners and weak points that are prone to breakage, which reduces the strength of the negative electrode current collector 10.

[0087] In some embodiments of this application, the area S1 of the first active material layer 21 covering the negative electrode current collector 10 and the area S0 of the negative electrode current collector 10 satisfy 60% ≤ S1 / S0 ≤ 90%. To balance the specific capacity of the negative electrode and the internal resistance of the electrochemical device, S1 / S0 should not be less than 60%. When it is less than 60%, the specific capacity of the negative electrode is relatively low, which may lead to adverse phenomena such as lithium plating during the cycling process of the electrochemical device. When S1 / S0 is greater than 90%, the impedance of the electrochemical device is high, resulting in a longer full charge time, making it difficult to meet the requirements of fast charging. The area S1 of the first active material layer 21 covering the negative electrode current collector 10 is within a suitable range to ensure the proportion of the first active material layer 21, thereby ensuring the energy density of the electrochemical device. Moreover, the area S1 of the first active material layer 21 covering the negative electrode current collector 10 is appropriate to reserve space for the current collector 10 and the second active material layer 22 to conduct, reduce the impedance of the electrochemical device, and improve the electrochemical performance of the electrochemical device. Therefore, the area S1 of the first active material layer 21 covering the negative electrode current collector 10 and the area S0 of the negative electrode current collector 10 satisfy 60% ≤ S1 / S0 ≤ 90%, which can take into account both the cycle performance and energy density of the electrochemical device.

[0088] In some embodiments, the area S1 of the first active material layer 21 covering the negative electrode current collector 10 and the area S0 of the negative electrode current collector 10 satisfy 60% ≤ S1 / S0 ≤ 90%, and the area S1 of the first active material layer 21 covering the negative electrode current collector 10 and the area S0 of the negative electrode current collector 10 satisfy 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, or other ranges formed by any two of the above endpoints.

[0089] Optionally, the area S1 of the first active material layer 21 covering the negative electrode current collector 10 and the area S0 of the negative electrode current collector 10 satisfy 70% ≤ S1 / S0 ≤ 80%.

[0090] In some embodiments of this application, the silicon-containing particles account for 50% to 98% of the total mass of the first active material layer 21. This suitable proportion of silicon-containing particles results in an electrochemical device with a high energy density formed by the first active material layer 21.

[0091] Optionally, the silicon-containing particles account for 60% to 95% of the total mass percentage of the first active material layer 21.

[0092] In some embodiments of this application, the silicon-based particles are selected from one or more of elemental silicon, silicon alloys, silicon-carbon composites, and silicon oxide materials.

[0093] In some embodiments of this application, the first active material layer 21 further includes a first adhesive, which is selected from one or more of polypropylene, polyacrylate, acrylonitrile copolymer and carboxymethyl cellulose salt.

[0094] In some embodiments of this application, a first binder with a relatively high content and high adhesion is added to the first active material layer 21 to suppress the expansion of the first binder. However, a first binder with a relatively high content and high adhesion will result in a large internal resistance of the battery, thereby weakening the electrical performance. Therefore, a first through-hole 211 is reserved in the first active material layer 21, and a second active material layer 22 containing carbon-based particles is formed on the first active material layer 21. The rate capability and cycle performance of the second active material layer 22 are better than those of the first active material layer 21 containing silicon-based particles. The second active material layer 22 is in direct contact with the negative electrode current collector 10 through the first through-hole 211, which can effectively give full play to the advantages of the rate capability and cycle performance of the second active material layer 22, thereby mitigating the defect of reduced electrical performance caused by the addition of a first active material layer 21 with a relatively high content and high adhesion. In addition, compared with mixed monolayers such as graphite, silicon, or silicon alloys, the first active material layer 21 uses a first binder with stronger adhesion. The first binder can restrain the expansion of the silicon-based particles in the first active material layer 21 during cycling. The adhesive used in the first active material layer 21 is a polypropylene, polyacrylate, acrylonitrile copolymer and carboxymethyl cellulose salt, which have high adhesion. It has low swelling in the electrolyte and can maintain high adhesion, effectively suppressing the volume expansion of silicon-based particles during charging and lithium intercalation.

[0095] Optionally, the first binder is a polymer selected from one or more monomers selected from acrylate, acrylate, acrylamide and acrylate.

[0096] In some embodiments of this application, the first active material layer 21 further includes a first conductive agent, which is selected from one or more of conductive carbon black (Super P), carbon fiber, graphene, or carbon nanotubes (CNTs). When the first active material layer 21 includes silicon-containing particles, a first binder, and a first conductive agent, the mass ratio of the silicon-containing particles, the first binder, and the first conductive agent is (85%–97%):(2%–10%):(1%–5%).

[0097] In some embodiments of this application, the thickness of the first active material layer 21 is 3 μm to 12 μm. The first active material layer 21 has a suitable thickness to ensure that the first active material layer 21 has a high electron mobility rate, and the suitable thickness of the first active material layer 21 also makes the silicon-containing particles have a high total mass, thereby achieving a high energy density.

[0098] In some embodiments, the thickness of the first active material layer 21 is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or other ranges consisting of any two of the above endpoints.

[0099] Optionally, the thickness of the first active material layer 21 is 3 μm to 10 μm.

[0100] In some embodiments of this application, the adhesion strength between the first active material layer 21 and the negative electrode current collector 10 is greater than or equal to 150 N / m. When the content of the first binder in the first active material layer 21 is high, the adhesion strength of the first active material layer 21 is good, enabling the first active material layer 21 to adhere stably to the negative electrode current collector 10. Therefore, a suitable first binder content can ensure that the adhesion strength of the first active material layer 21 is greater than or equal to 150 N / m. However, it is necessary to further control the content of the first binder to reduce the impact on lithium-ion diffusion and the reduction in the performance of the negative electrode sheet when the content of the first binder is too high.

[0101] Optionally, the adhesion force between the first active material layer 21 and the negative electrode current collector 10 is greater than or equal to 150 N / m.

[0102] Alternatively, the adhesion force between the first active material layer 21 and the negative electrode current collector 10 is greater than or equal to 300 N / m.

[0103] In some embodiments of this application, the carbon-based particles are selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, and mesophase carbon microspheres.

[0104] In some embodiments of this application, the second active material layer 22 further includes a second adhesive selected from one or more of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic acid (PAA).

[0105] In some embodiments of this application, the second active material layer 22 further includes a second conductive agent, one or more of conductive carbon black Super P, carbon fiber, carbon nanotubes (CNTs), acetylene black, conductive graphite, and graphene.

[0106] In some embodiments of this application, the second active material layer 22 further includes other additives, such as leveling agents, dispersants, thickeners, surfactants, etc. When the second active material layer 22 includes carbon-based particles, a second binder, a second conductive agent, and other additives, the mass ratio of the carbon-based particles, the second binder, the second conductive agent, and other additives is (92%–98%):(1%–3%):(1%–3%):(0%–2%).

[0107] In some embodiments of this application, the thickness of the negative electrode active material layer is 20 μm to 60 μm. The appropriate thickness of the negative electrode active material layer ensures the charging capability of the entire chemical system.

[0108] Optionally, the thickness of the second active material layer 22 is greater than or equal to the thickness of the first active material layer 21.

[0109] In some embodiments of this application, the ratio of the single-sided unit area capacity of the first active material layer 21 to the second active material layer 22 is 1:(1-4). A suitable ratio of the single-sided unit area capacity of the first active material layer 21 to the second active material layer 22 effectively reduces the risk of a large proportion of the first active material layer 21, which has relatively poor kinetics, leading to a deterioration in the overall kinetics.

[0110] Preparation method of negative electrode sheet

[0111] This application provides a method for preparing a negative electrode sheet, including:

[0112] S1. A first active slurry containing at least silicon-based particles is provided, and a first active material layer 21 is formed on the negative electrode current collector 10 by the first active slurry to obtain a composite, wherein the first active material layer 21 includes a plurality of first through holes 211 disposed at intervals through the first active material layer 21 along the thickness direction of the negative electrode current collector 10.

[0113] S2. A second active slurry containing at least carbon-based particles is provided, and a second active material layer 22 is formed on the composite by the second active slurry to obtain a negative electrode sheet, wherein the second active material layer 22 is at least disposed on the surface of the negative electrode current collector 10.

[0114] According to an embodiment of the negative electrode preparation method of this application, a first active slurry is first prepared to form a composite having a first active material layer 21 on the negative electrode current collector 10, and then a second active slurry is prepared to form a second active material layer 22 on the composite. This arrangement is beneficial for forming a first through hole 211 in the first active material layer 21, and also facilitates the adjustment of the first active material layer 21 and the second active material layer 22 respectively, resulting in high flexibility in production and manufacturing.

[0115] In some embodiments of this application, after the first active slurry is coated, it is dried to directly form a first active material layer 21 with first through holes 211; or, after the first active slurry is coated, it is dried to form a base film, and then holes are opened on the base film to form the first active material layer 21 with first through holes 211. The coating method of the first active material layer 21 is selected from one of gravure printing, microgravure printing, screen printing, roller printing, electro-spraying, transfer coating or extrusion coating.

[0116] For example, the coating method of the first active material layer 21 is gravure coating. By designing parameters such as the area ratio and shape of the recessed area and the non-recessed area in the gravure roller, a first active material layer 21 with a certain coating structure design can be coated. When the gravure roller has a non-recessed area of ​​a certain shape, a through-hole area of ​​the corresponding shape will be left in the first active material layer 21; when the gravure roller has a recessed area of ​​a certain shape, a coating area of ​​the corresponding shape will be left in the first active material layer 21.

[0117] Optionally, the drying temperature of the first active slurry is 80°C to 150°C.

[0118] In some embodiments of this application, the second active slurry is coated on the surface of the first active material layer 21, and the second active slurry can penetrate into the first through hole 211 and contact the negative electrode current collector 10. The coating method of the second active slurry is selected from extrusion coating, microgravure, transfer coating, gravure printing, etc.

[0119] For example, the second active material layer 22 is coated by extrusion coating, in which the second active slurry is attached to the first active material layer 21 and the negative electrode current collector 10 by extrusion coating, and then dried to form the second active material layer 22.

[0120] Optionally, the drying temperature of the second active slurry is 80°C to 150°C.

[0121] In some embodiments of this application, the negative electrode current collector 10 is provided with a plurality of spaced-apart second through holes 11. The method for preparing the second through holes 11 includes: creating pores in the negative electrode current collector 10 to obtain a negative electrode current collector 10 with second through holes 11. First, the second through holes 11 are formed on the negative electrode current collector 10, and then a first active slurry is coated on the negative electrode current collector 10. The second through holes 11 correspond to the uncoated areas of the first active slurry, so as to form first through holes 211 in the first active material layer 21.

[0122] In other embodiments of this application, the negative electrode current collector 10 is provided with a plurality of spaced-apart second through holes 11, and the method for preparing the second through holes 11 includes:

[0123] The composite is perforated to obtain a negative electrode current collector 10 with a second through hole 11, and a first through hole 211 is formed on the first active material layer 21. First, a first active slurry is coated on the negative electrode current collector 10 to form a composite with a first through hole 211. The negative electrode current collector 10 is perforated through the first through hole 211 to obtain the second through hole 11.

[0124] Positive electrode sheet

[0125] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector and including a positive active material.

[0126] It is understood that the positive electrode sheet can have a positive active material layer on one surface of the positive current collector, or it can have a positive active material layer on both surfaces of the positive current collector. This application does not make any special limitation on this.

[0127] The positive current collector can be a metal foil or a porous metal plate, such as foil or porous plate of metals or alloys thereof, such as aluminum, copper, nickel, titanium, iron, etc. In some embodiments of this application, the positive current collector is aluminum foil.

[0128] In some embodiments of this application, the positive electrode active material may be selected from at least one of the following: lithium manganese iron phosphate, lithium iron phosphate, lithium manganese phosphate, etc., olivine structure materials, NCM811, NCM622, NCM523, NCM333, etc., lithium cobalt oxide materials, lithium manganese oxide materials, and other metal oxides capable of lithium intercalation / deintercalation.

[0129] In some embodiments of this application, the positive electrode active material layer further includes an adhesive that enhances the bonding between the positive electrode active material particles and also enhances the bonding between the positive electrode active material and the current collector. Exemplarily, the adhesive may be selected from at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon.

[0130] In some embodiments of this application, the positive electrode active material layer further includes a conductive agent selected from at least one of carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. Exemplarily, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanotubes, or any combination thereof. The metal-based material is selected from metal powder, metal fibers, copper, nickel, aluminum, or silver. The conductive polymer is a polyphenylene derivative.

[0131] The positive electrode sheet in this application can be prepared according to conventional methods in the art. For example, the active material, conductive material and binder are dispersed in N-methylpyrrolidone (NMP) and mixed to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing, cutting, slitting and re-drying, the positive electrode sheet is obtained.

[0132] Separating membrane

[0133] The electrochemical device in this application embodiment may further include a separator membrane disposed between the positive electrode and the negative electrode to separate them and reduce the risk of direct contact between the negative and positive electrodes. The negative electrode, separator membrane, and positive electrode can have various structural forms; for example, the negative electrode, separator membrane, and positive electrode can be stacked sequentially to form a laminated structure, or the negative electrode, separator membrane, and positive electrode can be wound to form a wound structure.

[0134] The separator is a separator known in the art that can be used in electrochemical devices, such as, but not limited to, polyolefin microporous membranes. In some embodiments, the separator comprises at least one selected from polyethylene (PE), ethylene-propylene copolymer, polypropylene (PP), ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-methyl methacrylate copolymer.

[0135] In some embodiments, the separator is a single-layer separator or a multi-layer separator.

[0136] In some embodiments, the separator is coated with a coating. In some embodiments, the coating comprises at least one of an organic coating and an inorganic coating, wherein the organic coating is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyimide, acrylonitrile-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, acrylic-styrene copolymer, polydimethylsiloxane, sodium polyacrylate, and sodium carboxymethyl cellulose, and the inorganic coating is selected from at least one of SiO2, Al2O3, CaO, TiO2, ZnO2, MgO, ZrO2, and SnO2.

[0137] This application does not impose any particular limitations on the morphology and thickness of the separator. The method for preparing the separator is a well-known method in the art and can be used in electrochemical devices.

[0138] electrolyte

[0139] The electrochemical device in this application embodiment may further include an electrolyte. The electrolyte in this application contains an electrolyte salt. The electrolyte salt is a suitable electrolyte salt for electrochemical devices, known in the art. A suitable electrolyte salt can be selected for different electrochemical devices. For example, for lithium-ion batteries, lithium salts are typically used as the electrolyte salt.

[0140] In some embodiments, the lithium salt includes or is selected from at least one of organic lithium salts and inorganic lithium salts.

[0141] In some embodiments, the lithium salt includes or is selected from lithium hexafluorophosphate (LiPF6), lithium hexafluoroantimony oxide (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium perfluorobutyl sulfonate (LiC4F9SO3), lithium perchlorate (LiClO4), lithium aluminate (LiAlO2), lithium tetrachloroaluminate (LiAlCl4), and lithium bis(fluorosulfonyl imide) (LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2), where x and y are natural numbers, lithium chloride (LiCl), or lithium fluoride (LiF). In some embodiments, the mass percentage of lithium salt in the electrolyte of this application is 10 wt% to 15 wt%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, or any range therebetween.

[0142] The electrolyte of this application may also contain a non-aqueous organic solvent. In some embodiments, the non-aqueous organic solvent comprises at least one of carbonates, carboxylic esters, ether compounds, sulfone compounds, or other aprotic solvents. In some embodiments, the mass percentage of the non-aqueous organic solvent is 21% to 90%, for example, it can be 21%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or any range therebetween.

[0143] In some embodiments, the carbonate solvent comprises at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, ethylene carbonate, propylene carbonate, butene carbonate, and di(2,2,2-trifluoroethyl) carbonate.

[0144] In some embodiments, the carboxylic acid ester solvent comprises at least one of methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, γ-butyrolactone, valproic acid lactone, and butyrolactone.

[0145] In some embodiments, the ether compound solvent comprises at least one selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, bis(2,2,2-trifluoroethyl) ether, 1,3-dioxane, and 1,4-dioxane.

[0146] In some embodiments, the sulfone compound comprises at least one of ethyl vinyl sulfone, methyl isopropyl sulfone, isopropyl sec-butyl sulfone, and sulfolane.

[0147] The non-aqueous organic solvent in the electrolyte can be a single non-aqueous organic solvent or a mixture of multiple non-aqueous organic solvents. When using a mixed solvent, the mixing ratio can be controlled according to the desired performance of the electrochemical device.

[0148] The electrolyte of this application may also contain functional additives, such as film-forming additives and positive electrode film-forming additives. Film-forming additives can form an interfacial film on the surface of the negative electrode and / or the positive electrode, thereby protecting the negative electrode and / or the positive electrode. In some embodiments, the film-forming additives may be polynitrile additives, sulfonate additives, etc.

[0149] case

[0150] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrode. The electrode assembly is then obtained by winding. The electrode assembly is placed inside the housing, and then an electrolyte is injected. After vacuum sealing, settling, formation, and degassing molding, an electrochemical device is obtained.

[0151] The housing can be a rigid housing or a flexible housing. For example, a rigid housing can be made of metal. A flexible housing can be made of a metal-plastic film, such as aluminum-plastic film or steel-plastic film.

[0152] Electronic devices

[0153] A second aspect of this application provides an electronic device that includes the electrochemical device provided in the first aspect of this application. The electrochemical device provided in this application not only possesses excellent high-temperature storage performance and high-temperature cycling performance, but also high energy density, thus providing the electronic device with excellent high-temperature storage performance, high-temperature cycling performance, and high energy density.

[0154] This application does not impose any particular limitation on the electronic device used; it can be any electronic device known in the prior art. In some embodiments of this application, the electronic device may include, but is not limited to, laptops, pen-based computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, or lithium-ion capacitors, etc.

[0155] Example

[0156] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0157] For ease of explanation, the following examples use a lithium-ion secondary battery as an example to describe the electrochemical device and its manufacturing method in detail.

[0158] Examples 1 to 17, Comparative Examples 1 to 3

[0159] Example 1

[0160] Preparation of lithium-ion batteries

[0161] (1) Preparation of negative electrode

[0162] a) A mixture of silicon, acrylate, and electrostatic carbon black (Super P) in a mass percentage of 94%:4%:2% using water as the solvent was prepared and dispersed using a planetary mixer to form a first active slurry. This first active slurry was then coated onto both surfaces of the negative electrode current collector using a patterned gravure roller with localized non-dimpled areas. On the non-dimpled areas of the gravure roller, the first active slurry was scraped off by a doctor blade, corresponding to the areas on the negative electrode current collector where the first active slurry was not coated (i.e., the locations of the first through-holes). On the areas with depressions, the first active slurry was retained after scraping and transferred to the surface of the negative electrode current collector. The first active slurry is coated on the negative electrode current collector, and after drying and cold pressing in an oven at 100°C, a first active material layer is formed to obtain a composite. The first active material layer includes a first through hole that penetrates the first active material layer along the thickness direction of the negative electrode current collector. The area S1 of the first active material layer covering the negative electrode current collector and the area S0 of the negative electrode current collector satisfy S1 / S0 = 70%. The thickness of the first active material layer is 3μm, and the adhesion force between the first active material layer and the negative electrode current collector is greater than 300N / m.

[0163] b) Graphite, styrene-butadiene rubber (SBR), and carbon nanotubes (CNTs) were mixed in a mass percentage of 94%, 4%, and 2% with water as the solvent. The mixture was dispersed using a planetary mixer to prepare a second active slurry. The second active slurry was then coated onto the surface of the first active material layer by extrusion coating. The second active slurry penetrated into the first through-hole and came into contact with the negative electrode current collector. The mixture was then dried in an oven at 100°C to form the second active material layer. The thickness of the negative electrode active material layer was 47.5 μm, thus obtaining the negative electrode sheet.

[0164] The preparation methods of Examples 2 to 12 and Comparative Examples 1 to 3 are similar to those of Example 1, except that the first active material layer covers at least one of the area S1 of the negative electrode current collector, the area S0 of the negative electrode current collector, and the thickness of the first active material layer.

[0165] The relevant parameters of Examples 1 to 12 and Comparative Examples 1 to 3 are shown in Table 1.

[0166] Examples 13 to 17

[0167] The preparation method is similar to that of Example 1, except that a second through hole is provided on the negative electrode current collector. Multiple second through holes are obtained by drilling holes in the negative electrode current collector, and each second through hole is set in correspondence with each first through hole, as shown in Table 2.

[0168] (2) Preparation of the positive electrode

[0169] Lithium cobalt oxide (LiCoO2), carbon nanotubes (CNTs), and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) solvent at a weight ratio of 95:2:3. The mixture was stirred under vacuum to form a uniform positive electrode slurry. The positive electrode slurry was then uniformly coated onto aluminum foil as a positive electrode current collector. After drying at 85°C, the foil was cold-pressed, cut, and slit. Finally, it was dried under vacuum at 85°C for 4 hours to obtain the positive electrode sheet.

[0170] (3) Electrolyte preparation

[0171] In a dry argon-atmospheric glove box, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:3:6. Additives were then added, dissolved, and thoroughly stirred before lithium salt LiPF6 was added and mixed evenly to obtain the electrolyte. The concentration of LiPF6 was 1.20 mol / L.

[0172] (4) Preparation of the separating membrane

[0173] Boehmite was mixed with polyacrylate and dissolved in deionized water to form a coating slurry. The coating slurry was then uniformly coated onto both surfaces of a porous substrate using a microgravure coating method, and dried to obtain the desired release film.

[0174] (5) Preparation of lithium-ion batteries

[0175] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. Then, they are wound up and the tabs are welded to obtain a bare cell. The bare cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected. After vacuum sealing, settling, formation, shaping, and capacity testing, a soft-pack lithium-ion battery is obtained.

[0176] Performance testing:

[0177] (1) Measurement of the thickness of the first active material layer

[0178] In an environment of (25±5)℃, take a negative electrode current collector with only the first active material layer and a negative electrode current collector; use a micrometer to measure the thickness of the coating at least 10 different points of the negative electrode current collector, and record the average thickness of all test points as T0; use a micrometer to measure the thickness of the negative electrode current collector with the first active material layer at least 10 different points, and record the average thickness of all test points as T1; in particular, it is required that the micrometer measuring head must avoid falling into the area of ​​the first through hole; the thickness of the first active material layer is: T1-T0.

[0179] (2) Measurement of the thickness of the negative electrode active material layer

[0180] In an environment of (25±5)℃, take a negative electrode current collector with only the first active material layer and the second active material layer and a single negative electrode current collector; use a micrometer to measure the thickness of the coating at least 10 different points of the negative electrode current collector, and record the average thickness of all test points as T0; use a micrometer to measure the thickness of the negative electrode current collector with the first active material layer and the second active material layer at at least 10 different points, and record the average thickness of all test points as T2; the total thickness of the active material layer is: T2-T0.

[0181] (3) Adhesion

[0182] The adhesion between the first active material layer and the negative electrode current collector was tested using a high-speed rail tensile testing machine and the 90° angle method.

[0183] Fabrication of the negative electrode sheet for testing: Avoid attaching double-sided tape to the negative current collector without the first active material layer, as this will affect the adhesion test. Use a wire bar coating machine to fabricate a negative electrode sheet with a single-sided first active material layer completely covering the current collector. The first active material layer should be 4 μm thick for adhesion testing. Form the negative electrode sheet coated with the first active material layer into a strip. Along its length, attach a portion of the negative electrode sheet to a steel plate using double-sided tape from one end. Fix the steel plate to the corresponding position on the high-speed rail tensile testing machine. Pull up the negative electrode sheet not attached to the steel plate and clamp it in the clamp using a connector or directly. When the clamping tension is greater than 0 kgf and less than 0.02 kgf, the high-speed rail tensile testing can begin. The final average tensile force in the stable region is recorded as the adhesion force between the first active material layer and the current collector.

[0184] (4) The area S1 of the first active material layer covering the negative electrode current collector accounts for a certain percentage of the area S0 of the negative electrode current collector.

[0185] Take a certain area of ​​negative electrode current collector coated with the first active material layer; place the negative electrode current collector under a CCD lens and take an image of the current collector, where the dark area in the image represents the first active material layer and the bright area represents the empty negative electrode current collector; use software to calculate the dark area within the image's field of view as S1, which is the area of ​​the area coated with the first active material layer within the field of view; calculate the total area S0 of the field of view (including the area of ​​the dark area), which is the area of ​​the negative electrode current collector within the field of view; the ratio of the area S1 covered by the first active material layer to the area S0 of the negative electrode current collector is: S1 / S0.

[0186] (5) Theoretical specific capacity of the negative electrode active material layer

[0187] A negative electrode sheet coated only with a first active material layer or a first active material layer is fabricated and cut into circular pieces with areas s1 and s2, and coating weights m1 and m2, respectively. These are then assembled into a lithium-ion secondary battery. Charge-discharge tests are performed on the lithium-ion secondary battery to measure the lithium-ion secondary battery capacity C1 of the first active material layer and the lithium-ion secondary battery capacity C2 of the second active material layer. The first and second active material layers are coated with weights M1 and M2 in an area of ​​area S. The theoretical specific capacity per unit area of ​​the negative electrode active material layer containing both the first and second active material layers is shown in the following formula:

[0188]

[0189] (6) Cycle life test of lithium-ion batteries

[0190] Place the lithium-ion battery in an environment with a temperature of 25±3℃; charge it at a constant current rate of 1C to a voltage of 4.45V, and continue charging at 4.45V with a constant voltage until the current is ≤0.025C and then stop charging. Then discharge it at a constant current rate of 0.5C until the voltage is ≤2.75V; this is recorded as one charge-discharge cycle. Repeat the above steps until the capacity of the lithium-ion battery is less than 80%; the number of cycles at this point is the cycle life of the lithium-ion battery.

[0191] (7) Lithium-ion internal resistance test

[0192] Place the lithium-ion battery in an environment with a temperature of 25±3℃; connect a rated AC power supply (sine wave, 1000Hz frequency, current I of 10mA) and a voltmeter to the two ends of the battery; measure the voltage U across the battery using the voltmeter, then the AC internal resistance of the battery Rcell≈Rtest=U / I.

[0193] Performance test results:

[0194] Table 1. Components, related parameters, and performance of Examples 1 to 12 and Comparative Examples 1 to 3.

[0195]

[0196] Table 2. Components, related parameters, and performance of Examples 2, 1 / 3 to 17, and Comparative Example 1.

[0197]

[0198] As shown in Tables 1 and 2, the negative electrode sheets in Examples 1 to 17 have good specific capacity, full charge time, and cycle life. The negative electrode active material layer of the negative electrode sheet in this application includes a first active material layer and a second active material layer. The first active material layer includes silicon-based particles. Since the theoretical specific capacity of silicon-based particles is high, the reversible specific capacity of the negative electrode sheet is high. Moreover, the rate capability and cycle performance of the second active material layer containing carbon-based particles are better than those of the first active material layer containing silicon-based particles. The second active material layer is in direct contact with the negative electrode current collector through the first through-hole, which can effectively give full play to the advantages of the rate capability and cycle performance of the second active material layer, thereby alleviating the defect of reduced electrical performance caused by the addition of a first active material layer with a relatively high content and high adhesion of the first binder.

[0199] The performance test results in Table 1 show that, compared with Examples 2, 8 to 11 and Comparative Example 2, when the thickness of the first active layer material remains unchanged, the negative electrode using a pure silicon system has a higher specific capacity, but the cycle life is significantly reduced and the internal resistance is increased. As the coverage area of ​​the first active material layer silicon in the negative electrode current collector decreases, that is, the contact area between the second active material layer silicon and the negative electrode current collector increases, the battery internal resistance gradually decreases, effectively reducing the impedance of the electrochemical device and thus improving the cycle life of the electrochemical device. Compared with Examples 2, 8 to 11 and Comparative Example 3, the silicon-containing system has an advantage in specific capacity. Therefore, lithium-ion batteries made using the negative electrode of this application can maintain a balance between cycle life and specific capacity.

[0200] Compared with Comparative Example 1, Example 2 does not have a first through hole, and the lithium-ion battery prepared using the negative electrode sheet of the application has a higher cycle life and lower internal resistance.

[0201] Compared to Example 12, Example 2 improves the adhesion between the first active material layer and the negative electrode current collector, resulting in a longer cycle life for the lithium-ion battery. Higher adhesion of the first active material layer helps to restrain the expansion of silicon during charging and discharging. However, the expansion of the first active material layer leads to the pulverization and shedding of the negative electrode, worsening the adhesion between the first active material layer and the negative electrode current collector. This results in repeated damage and growth of the SEI on the negative electrode surface, consuming a large amount of electrolyte, generating more and more side reactions, and ultimately causing a sharp decline in cycle performance.

[0202] As further seen in Examples 1 to 7, by controlling the thickness of the first active material layer and reserving a certain uncoated area (i.e., the first through-hole) for coating the second active material layer, the thicker the first active material layer, the greater the internal resistance of the electrochemical device, and the battery cycle performance will gradually decrease. In order to balance the cycle performance and the specific capacity of the negative electrode active layer, the thickness of the first active material layer is controlled within a certain range when the coverage area of ​​the silicon in the first active material layer on the negative electrode current collector is fixed. This can balance the specific capacity and cycle performance of the negative electrode active material layer, preferably 3 to 5 μm. Referring to Comparative Example 1, Examples 2 and 13 to 17, the negative electrode current collector is provided with a second through-hole. The second through-hole provides an additional current channel for the outer second active material layer. Compared with Comparative Example 1, the internal resistance of the electrochemical device is smaller, reducing the impedance of the electrochemical device and eliminating the poor electrical performance of the first active material layer. Compared with Examples 2 and 13, due to the second through-hole, the impedance of the electrochemical device is further reduced, and the impedance and cycle performance of the second active material layer and the overall electrochemical device can be adjusted to a certain extent.

[0203] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present application, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A negative electrode plate, comprising: Negative electrode current collector; as well as A negative electrode active material layer includes a first active material layer and a second active material layer. The first active material layer is disposed on the surface of the negative electrode current collector and includes a plurality of spaced first through-holes extending through the first active material layer along the thickness direction of the negative electrode current collector. The second active material layer is disposed on the surface of the first active material layer and at least partially passes through the first through-holes to contact the surface of the negative electrode current collector. The second active material layer includes a base layer and an extension connected to the base layer and protruding relative to the base layer. The base layer is disposed on the surface of the first active material layer opposite to the negative electrode current collector, and the extension is disposed within the first through-holes and extends to the surface of the negative electrode current collector. The first active material layer comprises silicon-based particles; The second active material layer comprises carbon-based particles; The negative electrode current collector includes a plurality of second through holes spaced apart along the thickness direction of the negative electrode current collector. The second through holes communicate with the first through holes, and the extension extends into the second through holes.

2. The negative electrode sheet according to claim 1, wherein, The opening shape of each of the first through holes and the second through holes is independently selected from rectangles, squares, circles, ellipses, rhombuses, cones, strips, or triangles.

3. The negative electrode sheet according to claim 1, wherein, The area S1 of the first active material layer covering the negative electrode current collector and the area S0 of the negative electrode current collector satisfy 60%≤S1 / S0≤90%.

4. The negative electrode sheet according to claim 3, wherein, The area S1 of the first active material layer covering the negative electrode current collector and the area S0 of the negative electrode current collector satisfy 70%≤S1 / S0≤80%.

5. The negative electrode sheet according to claim 1, wherein, The silicon-based particles are selected from one or more of elemental silicon, silicon alloys, silicon-carbon composites, and silicon oxide materials.

6. The negative electrode sheet according to claim 1, wherein, The carbon-based particles are selected from one or more of artificial graphite, natural graphite, soft carbon, hard carbon, and mesophase carbon microspheres.

7. The negative electrode sheet according to claim 1, wherein, The negative electrode sheet satisfies one or more of the following (1) to (5): (1) The first active material layer further includes a first binder, wherein the first binder is selected from one or more of polypropylene, polyacrylate, acrylonitrile copolymer and carboxymethyl cellulose salt. (2) The first active material layer further includes a first adhesive, wherein the first adhesive is selected from polymers of one or more monomers selected from acrylonitrile, acrylate, acrylamide and acrylate; (3) The thickness of the first active material layer is 3 μm to 12 μm; (4) The adhesion force between the first active material layer and the negative electrode current collector is greater than or equal to 300 N / m; (5) The ratio of the single-sided unit area capacity of the first active material layer to that of the second active material layer is 1: (1 to 4).

8. The negative electrode sheet according to claim 1, wherein, The thickness of the first active material layer is 3 μm to 6 μm.

9. A method for preparing a negative electrode sheet, comprising: preparing the negative electrode sheet as described in any one of claims 1-8, comprising: A first active slurry containing at least silicon-based particles is provided, and a first active material layer is formed on a negative electrode current collector by the first active slurry to obtain a composite, wherein the first active material layer includes a plurality of first through holes disposed at intervals through the first active material layer along the thickness direction of the negative electrode current collector. A second active slurry containing at least carbon-based particles is provided, and a second active material layer is formed on the composite by the second active slurry to obtain a negative electrode sheet, wherein the second active material layer is at least disposed on the surface of the negative electrode current collector.

10. The method for preparing the negative electrode sheet according to claim 9, wherein, The negative electrode current collector has multiple spaced-apart second through holes, and the method for preparing the second through holes includes: A hole is formed in the negative electrode current collector to obtain the negative electrode current collector having the second through hole.

11. The method for preparing the negative electrode sheet according to claim 9, wherein, The negative electrode current collector has multiple spaced-apart second through holes, and the method for preparing the second through holes includes: The composite is perforated to obtain the negative electrode current collector having the second through hole, and the first through hole is formed on the first active material layer.

12. An electrochemical device comprising a negative electrode sheet according to any one of claims 1 to 8.

13. An electrochemical device comprising a negative electrode sheet prepared by any one of claims 9 to 11.

14. An electrical device comprising the electrochemical device of claim 12 or 13.

Citation Information

Patent Citations

  • Negative electrode pole piece and preparation method thereof, and lithium ion battery and preparation method thereof

    CN102820451A

  • Pole piece and lithium ion battery thereof

    CN109088050A